2017
DOI: 10.1073/pnas.1607883114
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genetic evidence for a unifactorial structure of spatial abilities

Abstract: Spatial abilities encompass several skills differentiable from general cognitive ability (). Importantly, spatial abilities have been shown to be significant predictors of many life outcomes, even after controlling for To date, no studies have analyzed the genetic architecture of diverse spatial abilities using a multivariate approach. We developed "gamified" measures of diverse putative spatial abilities. The battery of 10 tests was administered online to 1,367 twin pairs (age 19-21) from the UK-representativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
66
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 38 publications
(30 reference statements)
5
66
0
1
Order By: Relevance
“…We investigated the structure of spatial ability across a greater diversity of spatial tests. To this end, we 201 extended our analyses beyond the six tests of spatial orientation to incorporate 10 additional tests of object-202 based spatial skills 18 . This additional battery of spatial tasks included measures that very closely align with 203 traditional psychometric tests of spatial ability, including mental rotation, visualization, 2D and 3D drawing 204 ability, and mechanical reasoning.…”
Section: Substantial Associations Between Measures Of Spatial Orimentioning
confidence: 99%
See 3 more Smart Citations
“…We investigated the structure of spatial ability across a greater diversity of spatial tests. To this end, we 201 extended our analyses beyond the six tests of spatial orientation to incorporate 10 additional tests of object-202 based spatial skills 18 . This additional battery of spatial tasks included measures that very closely align with 203 traditional psychometric tests of spatial ability, including mental rotation, visualization, 2D and 3D drawing 204 ability, and mechanical reasoning.…”
Section: Substantial Associations Between Measures Of Spatial Orimentioning
confidence: 99%
“…In our previous work on the factor structure of object-based spatial tests, we have shown that individual 84 differences in spatial abilities cluster into a unitary factor, at both the observed and genetic levels, even after 85 accounting for g. 18 Along the same lines, another study found that the association between object-based and 86 spatial orientation abilities was largely independent of verbal ability. 15 These studies suggest that the coherence 87 of spatial abilities is not simply due to their being part of g, but rather inherent in the spatial domain itself.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…There are still some areas of research where traditional pen-and-paper approach may be more suitable (e.g. in some clinical populations or in rural areas where it is hard to get access to internet or even computer), but in general computer-based methods has proven to be adequate to such fields as behavioral genetics (Ismatullina & Voronin, 2017;Voronin, Ismatullina, Zaharov, & Malykh, 2016;Zakharov, Ismatullina, & Voronin, 2016;Rimfeld, et al, 2017), neuropsychology (Luciana, 2003), developmental psychology (Tikhomirova & Malykh, 2016), cross-cultural studies (Verbitskaya, Zinchenko, Malykh, & Tikhomirova, 2017) and others. Advantages of the computer-based tools include more convenient way to organize and store databases, standardized test administration or automated response recording.…”
Section: Introductionmentioning
confidence: 99%